Short-Length Raptor Codes for Free-Space Optical Communications - Zhang, Wenzhe (My University, 2009)
Free-space optical (FSO) links are competitive wireless links offering high data rate,
security and low system complexity. Compared to radio-frequency (RF) links, FSO
links offer high rates at gigabit-per-second (Gbps) level and relatively low cost. However, atmospheric scintillation and misalignment between optical transmitter and receiver impair data rates of FSO links. Scintillation and misalignment are slow fading
processes with a fading interval of 10's ms. Conventional fixed-length channel coding
which interleave data blocks are unrealistic to overcome this slow fading due to block
length of 10's of megabits. Also, because of the Gbps data rate, data rate adaptation
to channel conditions are expensive.
In this work, short-length (16 - 1024) Raptor codes are designed to overcome the
slow fading of FSO channels. These Raptor codes are applied at the packet-level with
high data rate and low decoding complexity. The Raptor encoder and decoder can be
easily implemented in any software or hardware form. The practicality of these Raptor
codes is demonstrated by a Raptor encoder and decoder which are implemented in
field-programmable gate array (FPGA) and shown to support a 1.22 Gbps encoding
and 714 Mbps decoding rate with a 97 mW low power consumption and 26360 gate
circuit scale. High-speed transmission at Gbps level is easily satisfied by the same
design implemented in an application-specific integrated circuit (ASIC).
Two applications of these short-length Raptor codes in FSO links are presented
in this work. Firstly, these Raptor codes are applied to hybrid FSO/RF links to
achieve high data rate by sending Raptor encoded packets simultaneously over the
FSO and RF links which we term such links as Raptor-coded soft-switching hybrid
FSO/RF links. The performance of these Raptor codes in the hybrid FSO/RF links
is simulated in a realistic channel model based on climate data of three Canadian
cities. For a 1 Gbps FSO link combined with a 96 Mbps WiMAX RF link, the softswitching
system achieves an average rate of 472 Mbps using the implemented Raptor
code while hard-switching technique achieves only 112 Mbps on average.
Secondly, these Raptor codes are applied in mobile FSO links for an unmanned
aerial vehicle (DAV). This mobile FSO link suffers from severe instantaneous misalignment. For packet-level transmission, the time varying misalignment is unknown
to the transmitter and causes data packet corruption and erasure. As a result, the
application of conventional fixed-rate erasure coding techniques is difficult. In this
work, short-length Raptor codes are applied in such mobile FSO channels. A key advantage of Raptor codes is their independence on channel state, no matter how large
the misalignment. With a 1 Gbps transmitter, the designed Raptor code with k = 64
message packets offers 650 Mbps data rate when transmitting power is 20 dEmo In
contrast, a traditional automatic repeat-request (ARQ) algorithm technique on the
same FSO jitter channel achieves a rate of 70 JVlbps.
Keywords: Electrical and Computer Engineering; Electrical and Computer Engineering